KASIH IBU (Edukasi Mengenai ASI Eksklusif dan MP-ASI Pada Ibu) At Posyandu Kenanga 1, Cipadu Village, Larangan District, Tangerang City : Program KASIH IBU (Edukasi Mengenai ASI Eksklusif dan MP-ASI Pada Ibu) Di Posyandu Kenanga 1, Kelurahan Cipadu, Kecamatan Larangan, Kota Tangerang - Anwar, Khoirul; Nanda, Elza; Permana, Juwita Cahaya; Sulistyaningsih, Lilis; Fitri, Yuni Pradilla; Maskar, Dadi H (Jurnal Pengabdian Masyarakat: Svasta Harena, 2023)
Wasting is one of the malnutrition that occurs in children and is a nutritional problem that is currently still occurring in Indonesia with the prevalence of wasting in Indonesia in 2021 namely 7.1% while in Tangerang City it is 5.9% in 2021. The purpose of the implementation of this program is to increase the knowledge of pregnant and lactating mothers at Posyandu Kenanga 1, Cipadu Village, Larangan District, Tangerang City regarding exclusive breastfeeding and complementary feeding. The method used in the implementation of this program is counseling and cooking demonstrations using leaflet as a media through 3 stages, namely the stages of preparation, implementation, and evaluation. Based on the implementation of the "KASIH IBU", it was found that there was an increase in knowledge of the respondents which was indicated by a P-value of 0.001 obtained through pre-test and post-test data. Based on the programs that have been carried out, it shows that there is an increase in knowledge of the respondents and respondents like the menu of the RUAS TOL which is demonstrated and respondents think that this program is well implemented, so that educational programs like this are important to do in order to increase knowledge in the community.